Co-delivery of paclitaxel and gemcitabine via a self-assembling nanoparticle for targeted treatment of breast cancer. Issue 10 (13th February 2019) - Lei, Meng; Sha, Sijia; Wang, Xueyuan; Wang, Jia; Du, Xiao; Miao, Hang; Zhou, Hui; Bai, Enhe; Shi, Jingmiao; Zhu, Yongqiang
Abstract : Preparation of MF-FA nanoparticles and the release behavior of drugs in tumor cells. Abstract : Multi-functional nanoparticles can be used to improve the treatment index and reduce side effects of anti-tumor drugs. Herein, we developed a kind of multi-functional and highly biocompatible nanoparticle (NP) loaded with folic acid (FA), paclitaxel (PTX) and gemcitabine (GEM) via self-assembly to target cancer cells. The transmission electron microscopy (TEM) results showed that multi-functional FA targeting nanoparticles (MF-FA NPs) exhibited spherical morphology and favorable structural stability in aqueous solution. In addition, NPs (MF-FA NPs and MF NPs) exhibited comparable proliferation inhibition to breast cancer cell 4T1 compared with the pure drug. In in vivo antitumor studies, NPs showed an obviously enhanced anti-tumor efficacy compared with the pure drug. Furthermore, MF-FA NPs displayed higher tumor growth inhibition than MF NPs due to the specific targeting of FA to cancer cells. Consequently, the novel MF-FA NPs could be used as a potential chemotherapeutic formulation for breast cancer therapy.